(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Budaya Pampang Village is an area in Samarinda City with a unique history, culture, tradition, and settlement because it contains the local wisdom values in its formation. This study aims to determine the concept underlying the unique pattern of settlement space formed using a qualitative inductive method with a phenomenological approach. The results showed that the uyen tiga philosophy contributed to the formation of a settlement space for the Dayak Kenyah community in the Budaya Pampang Village. This concept was formed based on the values contained in the uyen tiga philosophy, which consists of uyen tiga nangaliku kelunan and uyen tiga nangaliku panaq.